2013
DOI: 10.1002/ejoc.201300783
|View full text |Cite
|
Sign up to set email alerts
|

Practical First Total Synthesis of the Potent Phytotoxic (±)‐Naphthotectone, Isolated from Tectona grandis

Abstract: Naphthotectone is a quinone isolated recently from teak extracts of Tectona grandis. It has been shown to be one of the most abundant compounds and the most active compound isolated form teak. Thus, it has been proposed that naphthotectone is one of the compounds responsible for the allelophathic activity of this plant. An efficient total synthesis of (±)‐naphthotectone was achieved in seven steps and 31 % overall yield. The best results were obtained by using an aqueous Wittig reaction as a key step. Other re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…The enantiomeric excesses of diol 9 (92 % ee for S, 86 % ee for R) were determined by formation of the corresponding Omethylmandelate esters [13] followed by quantification by NMR spectroscopy (see Supporting Information). Esterification was carried out with the complementary S and R enantiomers, according to the method proposed by Trost et al [13b] Previously reported procedures were used to prepare three different substrates from 12 [4,14] in order to investigate the Sonogashira coupling with alkyne 2, as shown in Scheme 5. Vinyl bromide 15 was obtained in excellent yield by permethylation of 12 with dimethyl sulfate, oxidation to the quinone using ceric ammonium nitrate [15] (CAN), and bromination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enantiomeric excesses of diol 9 (92 % ee for S, 86 % ee for R) were determined by formation of the corresponding Omethylmandelate esters [13] followed by quantification by NMR spectroscopy (see Supporting Information). Esterification was carried out with the complementary S and R enantiomers, according to the method proposed by Trost et al [13b] Previously reported procedures were used to prepare three different substrates from 12 [4,14] in order to investigate the Sonogashira coupling with alkyne 2, as shown in Scheme 5. Vinyl bromide 15 was obtained in excellent yield by permethylation of 12 with dimethyl sulfate, oxidation to the quinone using ceric ammonium nitrate [15] (CAN), and bromination.…”
Section: Resultsmentioning
confidence: 99%
“…[3] We recently described the first total synthesis of racemic naphthotectone (1) from readily available starting materials. [4] The synthetic route was efficient, and involved a late-stage onepot anodic treatment and demethylation process to form the naphthoquinone core. In this paper, we describe two different enantioselective syntheses of this compound in which the aforementioned strategy is used, with the carbon side-chain of the naphthoquinone core being introduced by Pd coupling reactions (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the naphthoquinones were prepared from 47, which can easily be obtained from 38 by reduction with tin(II)chloride (Guerrero-Vásquez et al, 2013). Compounds 39, 40 and 41 were also prepared from 38 by acetylation and methylation.…”
Section: Chemistrymentioning
confidence: 99%
“…The synthesis of the naphthalene derivatives was performed as represented in Scheme . 2‐Formyl‐1,4,5,8‐tetramethoxynaphthalene ( 3 ) was prepared following and combining the procedures reported by Terada et al and Guerrero‐Vásquez et al . The reaction of 2‐formyl‐1,4,5,8‐tetramethoxynaphthalene ( 3 ) with nitromethane and t ‐BuOK as a base afforded the 2‐(1‐hydroxy‐2‐nitroethyl)‐1,4,5,8‐tetramethoxynaphthalene ( 4 ) as a racemic mixture.…”
Section: Resultsmentioning
confidence: 99%